Communities partnering with researchers: an evaluation of coalition function in a community-engaged research approach - Rockler, Briana E. (Kansas State University, 2015)
Background: Engaging community has become a fundamental approach to improving health outcomes in resource-limited settings. Community coalitions, comprised of resident activists that mobilize to improve local conditions, are frequently utilized as partners for community-engaged research. However, there is limited research that documents how these partnerships affect the coalitions. The purpose of this study was to evaluate the effects of researcher-coalition collaboration in the pilot year of a four-year intervention program targeting childhood obesity in rural, low-income communities. Methods: Twelve pre-established community coalitions from seven states were selected to partner with academic researchers in a quasi-experimental study, and then assigned to either the control (n=6) or intervention (n=6) group. Both study arms received funding and access to a menu of evidence-based tools, but the intervention groups were also provided a trained community coach. Member survey data from a Coalition Self-Assessment Survey (CSAS) tool was completed at baseline and at one-year follow-up. Results: CSAS data were analyzed to identify factors related to coalition function and efficacy, and significant changes in both experimental groups were identified. Change in measures of membership recruitment, coalition capacity and coalition communication were unique to the intervention group. Problems for participation were alleviated significantly on all measures in the control group. Comparison of the study groups at follow-up demonstrated that greater research involvement positively impacted membership recruitment and coalition action plan. Conclusion: The data suggest that coalitions with a higher degree of partnership interaction may be more successful in addressing problems impacting their communities.
Keywords: Community; Community-engaged research; Coalition; Childhood obesity; Coalition function; Nutrition (0570); Public Health (0573)